Dysbiosis: The first hit for digestive system cancer - Mei, Si; Deng, Zhe; Chen, Yating; Ning, Dimin; Guo, Yinmei; Fan, Xingxing; Wang, Ruoyu; Meng, Yuelin; Zhou, Qing; Tian, Xuefei (Frontiers in Physiology, 2022)
The digestive system cancer is suggested to be associated with the alteration of gut microbiota, known as dysbiosis. Understanding the role of gut microbiota in the development of digestive system cancer is useful for cancer prevention and gut microbiota-based therapy. However, the potential role of dysbiosis in the onset of tumorigenesis is not fully understood. While cumulating evidence demonstrates that dysbiosis in intestinal microbiota is present in both healthy and patients with various gastrointestinal (GI) diseases, severe GI dysbiosis are often present in patients with GI cancer. Importantly, some specific bacteria have been isolated from fecal samples of these patients. Thus, association between dysbiosis and the development of digestive system cancer can not be ignored. A new model describing their relationship has to be established. In this review, we postulate dysbiosis serves as the first hit for the development of digestive system cancer. Dysbiosis-induced alterations, including inflammation, aberrant immune response, bacteria-produced genotoxins, and cellular stress response associated with genetic, epigenetic and/or neoplastic changes, are second hits to speed up the carcinogenesis. Mechanisms for the above four pathways are explained in this review. Moreover, gut microbiota-based therapies are also discussed. The content included in this review will shed light on gut microbiota-based strategies for cancer prevention and therapy.